THE EFFECTS OF BUDGETING PERCEPTION AND KPUD PERFORMANCE INFLUENCE THE QUALITY OF LOCAL ELECTION (Empirical Study on The Regional Election Commissions at The District/City in Lampung Province) - matson suhari; Nelson Nelson (EKONOMI KEUANGAN DAN BISNIS, 2018)
The purpuse of this research is to know the effects of budgeting perception and KPUD Performance to influence The quality of local election on the County/city in lampung province. This research consisted of one hundred forty-two respondent there is members of the Komisi Pemilihan Umum Daerah (KPUD), Secretary of KPUD, sub-section head, and staff of KPUD on the County/city in lampung province. In the methode do applying for collecting data by angket. For processing data using the multiple regression analysis to know relation indefendent variable (X1) budgetingperception, (X2) KPUD Performance to influence defendant variable (Y) The quality of local election on the County/city in lampung province. The results of these research appeared that by significant 0,05 for two side test 2,5% and n =142 KPUD Performance is significance of  0,000, therefore budgeting perception and KPUD Performance has positive significant influences The quality of local election on the County/city in lampung province.